TOTAL FLAVONOID DAN EFEKTIVITAS EKSTRAK ETANOL BIJI KELOR (Moringa oleifera L) ASAL KOTA PALU SULAWESI TENGAH TERHADAP HISTOPATOLOGI PANKREAS TIKUS PUTIH JANTAN (Rattus norvegicus) YANG DIINDUKSI STREPTOZOTOCIN - Viani Anggi; Joni Tandi; Veronika Veronika (Jurnal Ilmiah Manuntung, 2020)
This study aims to determine the content of flavonoid and the effect of ethanol extract of moringa seeds on the regeneration of pancreatic β cells in male white rats streptozotocin induced diabetes. This study method used has total flavonoid equivalent quercetin by spectrophotometry uv-vis and to regeneration of pancreatic β cells in male white rats used 30 test animals,namely male white rats divided into 6 groups, each group consisted of 5 male white rats with details of group I as normal control, Group II as negative control given 0.5% Na-CMC suspension, Group III as positive control given glibenclamide suspension and in Groups IV, V, and VI were given with each dose of 100 mg/kg BW, 200 mg/kg BW and 400 mg/kg BB. Histopathological damage picture of the pancreas was observed by staining HE using a 400x magnification olympus Cx21 microscope. The results showed that the ethanol extract of moringa seeds contained secondary metabolites, namely flavonoids, alkaloids, saponins and tannins. The results showed has total flavonoid equivalent quercetin of moringa seeds is 1,26% and regeneration of pancreatic β cells in male white rats streptozotocin induced diabetes of Moringa seed ethanol extract at a dose of 400 mg/kg BB can have an effect on the regeneration of β cells in the pancreas of white diabetic male rats.